THE CONSTRUCTION OF RELIGIOSITY ROLE IN CAUSALITY RELATIONSHIP WITH CONSUMER BEHAVIOR INTENTION - Daru Asih; Ridho Bramulya Ikhsan; Nurul Komara Fajrin; Fadhila Dhia Malihah (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This study is intended to examine the role of religiosity in the causal relationship between the use of Instagram social media and the behavioral intentions of consumers towards culinary products, whether the role of the construct of religiosity in the relationship mediates or moderates. In addition, the purpose of this study was to examine the effect of using advertising through social media, in this case, Instagram, on the behavioral intentions of consumers on SME culinary products. The survey was conducted on 200 respondents using Instagram using the purposive sampling technique. Data analysis was performed using Structural Equation Modeling, with Smart PLS program.